Infaq Box Program (KOIN) in Improving the Role of Shodaqoh Based on Local Wisdom - Qurrotu Ayniy; Imam Mukhlis (Arkus, 2022)
Zakat, infaq, shadaqah and waqaf is an instrument used from the time of the Prophet and is one of the most effective instruments in overcoming economic problems. The government's step in developing the potential of the Islamic economy in Indonesia, which is based on a large Muslim population, is one of the early stages of the development of the Sharia system in Indonesia. The potential of ZISWAF has now been realized and has begun to be carried out both centrally and in the regions. UPZIS Lawang District is one of the non-profit regional institutions engaged in collecting infaq, shadaqah and zakat under LAZISNU Malang Regency. The motto of one day one thousand shadaqah gives its charm to the community. In addition, the collection of funds is carried out using methods that are not as common as other shodaqoh. The method used in this study is qualitative. Qualitative methods are used to see the community's knowledge of the institution and become a reference for assessing the opportunities and challenges in maximizing the potential of ZISWAF in the community. The existence of regional non-profit institutions can indirectly be one of the tools that can assist the government in the welfare of the surrounding community in various targeted fields.